2016
DOI: 10.1103/physrevb.94.224508
|View full text |Cite
|
Sign up to set email alerts
|

Competition of superconductivity with the structural transition inMo3Sb7

Abstract: Prior to the superconducting transition at T c ≈ 2.3 K, Mo 3 Sb 7 undergoes a symmetry-lowering, cubic-to-tetragonal structural transition at T s = 53 K. We have monitored the pressure dependence of these two transitions by measuring the resistivity of Mo 3 Sb 7 single crystals under various hydrostatic pressures up to 15 GPa. The application of external pressure enhances T c but suppresses T s until P c ≈ 10 GPa, above which a pressure-induced first order structural transition takes place and is manifested by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…Moreover, our calculated surface energy is 0.61 Jm À 2 , almost the same of the benchmark value (0.60 Jm À 2 ). Moreover, the calculated Ionization Potential (IP) is 7.12 eV reasonably close to the experimental value, 7.50 eV [72].…”
supporting
confidence: 75%
“…Moreover, our calculated surface energy is 0.61 Jm À 2 , almost the same of the benchmark value (0.60 Jm À 2 ). Moreover, the calculated Ionization Potential (IP) is 7.12 eV reasonably close to the experimental value, 7.50 eV [72].…”
supporting
confidence: 75%
“…It corresponds to the number of the edge modes [32]. For an interacting SSH model in the clean limit, the ES of the groundstate has been extensively studied to characterize the SPT groundstate by the ES [31,43]. In the clean limit, we confirmed that the SPT groundstate in the SSH model of H SSH with J 2 > J 1 and open boundary has two or fourfold degeneracy of the lowest ES depending on the system size L.…”
supporting
confidence: 65%
“…The pressure evolution of superconductivity in Mo 3 Sb 7 was measured using ac magnetic susceptibility ( Turning to structural information, the phase boundary T S (P) was tracked by macroscopic probes such as the electrical resistivity [27], where T S (P) is suppressed by increasing pressure (Figs. 1), but only slowly (~2.5K/GPa), remaining well above zero out to 12 GPa.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…We therefore believe that the main influence on T c should come from the electron-phonon coupling constant λ, with λ dependent on both electronic structure and the phonon dispersion spectrum [39]. The smoothly varying resistivity under pressure [27] indicates a continuously evolving electronic structure, consistent with estimated small difference between the tetragonal and cubic structures by theoretical calculation at ambient pressure [38]. Hence the origin of the doubled T c most likely arises from details of the symmetry-dependent phonon dispersion [39].…”
Section: Discussionmentioning
confidence: 99%